2019
DOI: 10.1177/0735633119867422
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Students’ Learning Style, Sense of Presence, and Cognitive Load on Learning Outcomes in an Immersive Virtual Reality Learning Environment

Abstract: The purpose of this study was to investigate the relationship among Taiwanese high school students’ learning style, sense of presence, cognitive load, and affective and cognitive learning outcomes in an immersive virtual reality-based learning environment. This study used a teaching experiment intervention method. Seventy-seven students participated in the virtual reality-based learning environment and completed related scales and a test. This study found that although the students’ learning style does not inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 49 publications
6
73
1
Order By: Relevance
“…e results of this study showed that VRI creates a high level of satisfaction among users. Similarly, previous studies have suggested that interactivity with advanced technology (VR) affects attitude and creates a positive attitude [94]. Moreover, researchers have expressed serious concerns about health and addiction toward Internet games.…”
Section: Practical Implicationsmentioning
confidence: 96%
“…e results of this study showed that VRI creates a high level of satisfaction among users. Similarly, previous studies have suggested that interactivity with advanced technology (VR) affects attitude and creates a positive attitude [94]. Moreover, researchers have expressed serious concerns about health and addiction toward Internet games.…”
Section: Practical Implicationsmentioning
confidence: 96%
“…According to the previous interpretation, the psychological learning traits may influence subjective engrossing experiences in the virtual learning context (Chu, Humer, & Eckhardt, 2019; Huang et al, 2020) and be related to learning perceptions and attitudes (Cai et al, 2019; Dindar & Akbulut, 2015; Hopp et al, 2015). The subjective engrossing experiences such as perceived immersion have also been verified as linking with perceptions of learning benefits and outcomes (Huang et al, 2010, 2016; Makransky & Lilleholt, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To have the participants experience a stronger sense of immersion, using head‐mounted displays (HMD) to support virtual reality applications is necessary. For example, the high‐end HMD headsets (eg, HTC Vive and Oculus Rift) have been utilized for biology learning (Huang, Luo, Yang, Lu, & Chen, 2020) and environmental education (Markowitz et al, 2018). However, for the implementation of IVR instruction or learning in classrooms, the setup of IVR with high‐end HMD requires certain exercise space for users to operate and hence may result in some practical limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECNU studies on the application of VR in face-to-face learning environments have identified an increase in the sense of students' presence and the relevance of visual processing in children's learning, revealing the importance of the use of new virtual technologies in curricula and teaching materials for these students. (Huang et al, 2020;Liu et al, 2020). As a way to better instruct pedagogy graduates on these technologies, ECNU developed for its pedagogy course the subject "Modern Education Technology," in which the main skills and competencies necessary for the use of ICT in teaching-learning are addressed (Lim et al, 2015).…”
Section: Academiamentioning
confidence: 99%